PERUBAHAN AKTIVITAS ENZIM LIPASE DARI BUAH KELAPA SELAMA PERTUNASAN - Moh. Su'i; Harijono; Yunianta; Aulani'am (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
This research learned about lipases activity from coconut during germination. Coconut was growth for 0, 15, 30, 45 and 60 days in the darkplace and rate temperature. Shoot, houstorium, radicless and endosperm were taken and then they were measured weigh and long. Lipases was extracted from each of them and measured volume and activity. The results of research showd that highest lipases activity was in shoot that were grew for 45 days with enzyme activity was 0,060 unit/mg protein.